Habits and Dispositions in Frank Ramsey’s Philosophy - Alice Morelli (European Journal of Analytic Philosophy)
This paper examines Ramsey’s use of the concepts of habit and disposition, challenging the common interpretation that he employs them interchangeably in his theory of belief. This interpretative trend reflects a broader tendency to equate habit and disposition, based on the assumption that a habit is an acquired disposition to act. However, the precise relationship between these concepts often remains underexplored and it is not clear whether habits are merely a subset of dispositions or if they are conceptually distinct. Using Ramsey’s writings as a case study, this paper argues that their relationship is more nuanced than a reductive equivalence suggests. I advance a twofold thesis: first, I argue that Ramsey’s use of the notions of habit and disposition is more complex than typically assumed, as he employs them in distinct philosophical contexts and conceptualizes them in different ways. Second, I distinguish between a logical-grammatical kind of dispositionalism and a metaphysical one to argue that the notion of habit is dispositional but habits are not metaphysically equivalent to dispositions. Ramsey conceptualizes habits as methods, rules, procedures of thought, whereas dispositions are understood as tendencies or inclinations engendered and shaped by habits.